Brivaracetam in the treatment of epilepsy: a review of clinical trial data - Feyissa AM (Dove Medical Press, 2019)
Anteneh M Feyissa Department of Neurology, Mayo Clinic, Jacksonville, FL, USACorrespondence: Anteneh M FeyissaDepartment of Neurology, Mayo Clinic, 4500 San Pablo Road, Jacksonville, FL 32224, USATel +1 904 953 7102Fax +1 904 953 0757Email Feyissa.Anteneh@mayo.eduAbstract: Brivaracetam (BRV), an analog of levetiracetam (LEV), was discovered during a target-based rational drug discovery program that aimed to identify potent synaptic vesicle protein 2A (SV2A) ligands. Among the 12,000 compounds screened in vitro, BRV was found to have 15–30 times greater affinity for SV2A and faster brain permeability than LEV. Although preclinical and post-marketing studies suggest broad spectrum of efficacy, BRV is currently only approved as monotherapy and adjunctive therapy of focal-onset seizures in patients age 4 years and older. This review examines the use of BRV as add‐on (5–200 mg/day) therapy for epilepsy with a particular emphasis on the six regulatory randomized clinical trialsinvolving 2399 participants. Participants receiving BRV add‐on at doses of 50–200 mg/day were more likely to experience a 50% or greater reduction in seizure frequency (pooled risk ratio [RR]) 1.79 with 95% CI of 1.51–2.12) than those receiving placebo. Participants receiving BRV were also more likely to attain seizure freedom (57 [3.3%] vs 4 [0.5%]; RR 4.74, 95% CI 2.00–11.25) than those receiving placebo. In addition, BRV demonstrated a favorable safety profile similar to placebo across all BRV doses. Treatment emergent adverse events significantly associated with BRV were irritability, fatigue, somnolence, and dizziness. Post-hoc analysis of regulatory trials, post-marketing studies, and indirect comparison meta-analyses demonstrated equivalent efficacy and better tolerability of BRV when compared to other antiseizure drugs. Further, these studies appear to suggest that behavioral adverse events are likely to be less frequent and less severe with BRV than LEV. Therefore, switching to BRV may be considered for patients who have seizure control with LEV, but who cannot tolerate its behavioral adverse effects. In this setting, immediate switch from LEV to BRV at a 10:1–15:1 ratio without titration is feasible. Further research is needed to examine the long-term tolerability and efficacy of BRV as well as its role in the treatment of other types of epilepsies, particularly dementia-related epilepsy and brain tumor-related epilepsy.Keywords: antiepileptic drugs; brivaracetam, drug-resistant epilepsy, focal epilepsy, levetiracetam, psychiatric adverse events